2005
DOI: 10.1007/s11046-005-0373-y
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and molecular diversity in Colletotrichum graminicola from Brazil

Abstract: Genetic diversity among 37 isolates of the sorghum anthracnose pathogen Colletotrichum graminicola, from four geographically distinct regions of Brazil, was evaluated by RAPD and RFLP-PCR markers and virulence characters on a set of 10 differential sorghum genotypes. Twenty-two races were identified and race 13B was the most frequent, but present in only two regions. RAPD analysis revealed 143 polymorphic bands that grouped the isolates according to their geographic origin, but not by their virulence phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…According to Ali and Warren, [2], Thomas, [26], and Hess et al, [11], more intense sorghum anthracnose is associated with high temperature and relative humidity. During the growing season, the occurrence of unseasonal rainfall during the flowering and dough stage coupled with high to moderate temperature (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) o C) encouraged the development of the disease. In addition, the high variability of the pathogen populations made most sorghum fields without tolerance [27].…”
Section: The Prevalence Incidence and Severity Of Sorghum Diseasesmentioning
confidence: 99%
“…According to Ali and Warren, [2], Thomas, [26], and Hess et al, [11], more intense sorghum anthracnose is associated with high temperature and relative humidity. During the growing season, the occurrence of unseasonal rainfall during the flowering and dough stage coupled with high to moderate temperature (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) o C) encouraged the development of the disease. In addition, the high variability of the pathogen populations made most sorghum fields without tolerance [27].…”
Section: The Prevalence Incidence and Severity Of Sorghum Diseasesmentioning
confidence: 99%
“…in Kabat and Bubák) is the fungal pathogen responsible for sorghum anthracnose (Crouch et al, 2006) and was first reported in Togo, West Africa in 1902 (Thakur and Mathur, 2000). The disease occurs worldwide, but is more commonly observed in tropical or subtropical environments where frequent rainfall, high relative humidity and warm temperatures enhance the development and spread of the disease (Casela et al, 2001;Hess et al, 2002;Marley et al, 2001;Néya and Le Normand, 1998;Ngugi et al, 2002;Thakur and Mathur, 2000;Thomas et al, 1996;Valério et al, 2005). In the United States, anthracnose is more prevalent in the Southern Plains and Southeastern States (Rosewich et al, 1998;Cardwell et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The disease can be successfully managed through the use of resistant cultivars. However, the long-term durability of resistant cultivars is hindered by variation in virulence within the pathogen population Cardwell et al, 1989;Marley et al, 2001Pande et al, 1991Thakur and Mathur, 2000;Valério et al, 2005). Pyramiding of resistance genes can aid in the development of resistant cultivars, but additional sources of resistance are needed for sorghum improvement.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, the use of resistant varieties is recommended for regions with climatic conditions favorable for the pathogen. Since the pathogen is highly variable and numerous pathotypes are present in most regions (Marley et al, 2001;Valério et al, 2005), pyramiding of host-plant resistance genes may be necessary to increase the longevity of resistant sources. Thus, additional resistant germplasm is needed to increase the genetic diversity of resistant genotypes available for sorghum improvement.…”
Section: Introductionmentioning
confidence: 99%